Implementing Employability Skills Module in Aluminium Fabrication And Glazing Work In Nigerian Technical Colleges - Olusegun Olawale Olakotan; Jonathan Ojo Oke (Advanced Journal of STEM Education, 2023)
Facilities are essential ingredients for an all-round implementation of any skill-based programme in Technical and Vocational Education and Training. In this study, we want to ascertain the facilities that will be appropriate to implement employability skills module in aluminium fabrication in Nigerian technical colleges. Further, we employed Confirmatory Factor Analysis (CFA) to reveal that the identified facilities are appropriate for implementing employability skills module in aluminium fabrication having fulfilled all the conditions for convergent, construct and discriminant validity. Based on the findings of the study, it was recommended that the identified facilities be given priority and procured for the successful implementation of the employability skills module in aluminium fabrication and glazing work